The effect of Krill oil supplementation on blood glucose levels in alloxan-induced hyperglycemic rats - Nurmadilla, Nesyana; Nugraha Pratiwi, Anastasia; Bamahry, Aryanti; Sulvita, Nevi; Sodiqah, Yani (Gaceta Médica de Caracas, 2021)
Introduction: Hyperglycemia is a condition associated with long-term complications and damage of multiple susceptible organs, including the eye, kidney, nerve, and heart. Krill oil contains astaxanthin, which is an antioxidant that acts to fight free radicals. The study aims to determine the effect of krill oil supplementation on blood glucose levels of alloxan-induced hyperglycemic rats.